LPS induces CD40 gene expression through the activation of NF-κB and STAT-1α in macrophages and microglia - Qin, Hongwei (The American Society of Hematology, 2005)
CD40 is expressed on various immune cells, including macrophages and microglia. Aberrant expression of CD40 is associated with autoimmune inflammatory diseases such as multiple sclerosis and rheumatoid arthritis. Interaction of Toll-like receptor-4 (TLR4) with the Gram-negative bacteria endotoxin lipopolysaccharide (LPS) results in the induction of an array of immune response genes. In this study, we describe that LPS is a strong inducer of CD40 expression in macrophages and microglia, which occurs at the transcriptional level and involves the activation of the transcription factors nuclear factor-κB (NF-κB) and signal transducer and activator of transcription 1α (STAT-1α). LPS-induced CD40 expression involves the endogenous production of the cytokine interferon-beta (IFN-β), which contributes to CD40 expression by the activation of STAT-1α. Blocking IFN-β–induced activation of STAT-1α by IFN-β–neutralizing antibody reduces LPS-induced CD40 gene expression. Furthermore, LPS induces acetylation and phosphorylation of histones H3 and H4 and the recruitment of NF-κB, STAT-1α, and RNA polymerase II on the CD40 promoter in vivo in a time-dependent manner, all events important for CD40 gene transcription. These results indicate that both LPS-induced NF-κB activation and endogenous production of IFN-β that subsequently induces STAT-1α activation play critical roles in the transcriptional activation of the CD40 gene by LPS.